RELATIONSHIP BETWEEN WORK STRESS AND WORK MOTIVATION TOWARDS NURSE PERFORMANCE - M. Irsan Arief Ilham (Universitas Islam Negeri Alauddin Makassar, 2021)
Background: Data from the World Health Organization shows that the number of nurses in 2019 was around 19.3 million, while in Indonesia it was 147,264. The current ratio of nurses is 87.65 per 100,000 population, meaning that it is still very far from the national target of 180 per 100,000 population. The condition of nurses is still very limited, so it takes effort and motivation to improve the performance of nurses so that the nurses do not experience work stress.Objective:To analyze the relationship between work stress and work motivation on the performance of nurses at Puskesmas Malili Kab. East Luwu.Method:This study used a cross-sectional study design. The sampling technique in this study was to use accidental sampling on nurses at the Malili Public Health Center, East Luwu Regency.Result:The results showed that there was a relationship between job stress and work motivation on nurses' performance.Conclusion: Continuous efforts are needed to prevent work stress on nurses and increase motivation so that all nurses can perform well without high stress. Motivation is an important thing to pay attention to because it determines the performance of nurses. Hospital leaders are expected to instill a sense of responsibility towards nurses because their job is to serve patients.